HLA Pharmacogenetic Markers of Drug Hypersensitivity in a Thai Population - Nakkam, Nontaya; Konyoung, Parinya; Kanjanawart, Sirimas; Saksit, Niwat; Kongpan, Thachanan; Khaeso, Kanyarat; Khunarkornsiri, Usanee; Dornsena, Areerat; Tassaneeyakul, Wongwiwat; Tassaneeyakul, Wichittra (Frontiers in Genetics, 2018)
Severe cutaneous adverse drug reactions (SCARs) including Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), and drug reactions with eosinophilia and systemic symptoms (DRESS) are potentially life-threatening cutaneous reactions caused by several drugs. Recently, a number of genes encoding for human antigen presenting proteins, HLA alleles, have been discovered as valid pharmacogenetic markers for prediction of these life-threatening reactions. This study was aimed to determine the distribution of HLA alleles including the HLA class I and class II genes in 183 unrelated individuals of a Thai population using high resolution HLA genotyping in order to obtain 2-field data (4-digit resolution) and compare the frequencies of the HLA alleles that have been proposed as markers of SCARs with other ethnics. Results revealed a high prevalence of pharmacogenetic markers of drug-induced SCARs e.g., B*13:01 for dapsone; B*15:02 for carbamazepine and oxcarbazepine; B*58:01, A*33:03 and C*03:02 for allopurinol; C*08:01, C*14:02 and DRB1*12:02 for co-trimoxazole. Whereas, low prevalence of pharmacogenetic markers of SCARs induced by abacavir, B*57:01 and phenytoin, B*56:02/B*56:04 were noticed. The allele frequencies of B*13:01, B*15:02, and B*58:01 observed in a Thai population were significantly higher than those reported in Japanese and Caucasian populations. Similar to those observed in other Southeast Asian populations, low frequencies of A*31:01 and B*57:01 alleles were noted in the study population. Based on the frequencies of HLA pharmacogenetic markers, Thai and other Southeast Asian populations may at higher risk of drug-induced SCARs compared with Caucasian population.